Cranial ultrasound screening in term and late preterm neonates born by vacuum-assisted delivery: Is it worthwhile? - Dario Gallo; Ilia Bresesti; Angela Bossi; Donatella Lissoni; Antonella Cromi; Maria Luisa Tataranno; Lorenza Bertù; Fabio Ghezzi; Massimo Agosti (Elsevier, 2023)
Background: Vacuum extraction is the most common choice to assist vaginal delivery, but there are still concerns regarding the neonatal injuries it may cause. This study aimed to evaluate the rate of intracranial injuries assessed by cranial ultrasound (cUS) among infants born by vacuum extraction, and the relationship with maternal and perinatal factors. Methods: This was a single-center retrospective study carried out in a level-3 neonatal unit. A total of 593 term and late preterm infants born by vacuum-assisted delivery were examined with a cUS scan within 3 days after birth. Results: Major head injuries were clinically silent and occurred in 2% of the infants, with a rate of intracranial haemorrhage of 1.7%. Regardless of obstetric factors, the risk of cranial injury was increased in infants requiring resuscitation at birth (p = 0.04, OR 4.1), admitted to NICU (p = 0.01, OR 5.5) or with perinatal asphyxia (p < 0.01, OR 21.3). Maternal age ≥40 years correlated both with adverse perinatal outcomes (p < 0.05) and the occurrence of major injury (p = 0.02, OR 4.6). Conclusion: Overall, vacuum extraction is a safe procedure for neonates. Head injuries are usually mild and asymptomatic, and with spontaneous recovery. However, the rate of major cranial injuries in our cohort warrants further investigation to support a cUS screening, particularly for infants requiring respiratory support at birth. Also, maternal age might be taken into account when evaluating the risk for neonatal complications after vacuum application.